Wigner Crystal and Colossal Magnetoresistance in InSb Doped with Mn - Obukhov, S. A. (Sci Rep, 2015)
We report magnetotransport investigation of nonmagnetic InSb single crystal doped with manganese at Mn concentration N(Mn) ~ 1,5 × 10(17) cm(−3) in the temperature range T = 300 K–40 mK, magnetic field B = 0–25T and hydrostatic pressure P = 0–17 kbar. Resistivity saturation was observed in the absence of magnetic field at temperatures below 200 mK while applied increasing external magnetic field induced colossal drop of resistivity (by factor 10(4)) at B ~ 4T with further gigantic resistivity increase (by factor 10(4)) at 15T. Under pressure, P = 17 kbar, resistivity saturation temperature increased up to 1,2 K. Existing models are discussed in attempt to explain resistivity saturation, dramatic influence of magnetic field and pressure on resistivity with the focus on possible manifestation of three dimensional Wigner crystal formed in InSb by light electrons and heavy holes.